DRUG-INDUCED NEPHROPATHY IN PULMONARY TUBERCULOSIS PATIENTS WITH BURDENED ALLERGIC HISTORY - T. A. Kolpakova (Туберкулез и болезни лёгких)
112 tuberculosis patients with burdened allergic history were examined with the purpose to study clinical and laboratory manifestations of drug-induced nephropathy, they made main group and 157 patients without allergy made control group. Drug-induced renal lesion in tuberculosis patients with multiple allergies can be manifested in various ways: from microhematuria, minor eosinophilia and cutaneous allergic syndrome to major disorders of nitrogenous excretion, filtration and resorption function of kidneys leading to the development of acute and in some cases chronic renal failure. Laboratory rates reflecting renal function returned to normal later after recovery from other drug-induced complications not related to kidneys. Rifampicin was responsible for the development of nephropathy in the majority of patients, and in single cases it was streptomycin.